2021
DOI: 10.1007/s10989-021-10287-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multi-omics, Virtual Screening and Molecular Docking Analysis of Methicillin-Resistant Staphylococcus aureus USA300 for the Identification of Potential Therapeutic Targets: An In-Silico Approach

Abstract: Staphylococcus aureus infection is a leading cause of mortality and morbidity in community, hospital and live-stock sectors, especially with the widespread emergence of methicillin-resistant S. aureus (MRSA) strains. To identify new drug molecules to treat MRSA patients, we have undertaken to search essential proteins that are indispensable for their survival but nonhomologous to human host proteins. The current study utilizes a subtractive genome and proteome approach to screen the possible therapeutic target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 128 publications
0
3
0
Order By: Relevance
“…Earlier studies reported that PBP1 and PBP2 are considered potential therapeutic targets for their cellular importance. These proteins were found interacting with the staphylococcal femXAB family protein, mur-family proteins, Ddl, and MraY and play a curial role in the peptidoglycan biosynthesis pathway [ 57 , 58 ]. Also, these proteins have immunogenic properties and could be vaccine candidates in N. meningitidis [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies reported that PBP1 and PBP2 are considered potential therapeutic targets for their cellular importance. These proteins were found interacting with the staphylococcal femXAB family protein, mur-family proteins, Ddl, and MraY and play a curial role in the peptidoglycan biosynthesis pathway [ 57 , 58 ]. Also, these proteins have immunogenic properties and could be vaccine candidates in N. meningitidis [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The target enzyme MurE ligase is a complex molecule that initiates the peptidoglycan biosynthesis [ 83 ] by adding meso-diaminopimelic acid to the nucleotide precursor UDP-N-acetylmuramoyl-L-alanyl-D-glutamate during the synthesis of murein in the cytoplasm [ 84 ]. As this enzyme is vital to the survivability of S. aureus strains, it can be used as a potential antibacterial drug target [ 57 , 58 , 83 ]. Based on the interaction between the crystallographic structure of the MurE template (4C12 from S. aureus ) and the crystallographic ligand uridine 5′ diphospho N-acetyl muramoyl-L-Alanyl-D-Glutamyl-L-Lysine (UML), it was found that the active site residues involved in H-bond interactions were Ser456, Glu460, Asp406, Thr152, Ser179, Arg187, Arg383, His205, Asn151, Thr153, Thr45, Thr46, Val47, Thr28, Ser30, and Val47.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several other auxillary (aux) genes have also been identified that play a crucial role in methicillin resistance, namely, factors essential for methicillin-resistance (fem) family genes . Three of these genes, femX , femA, and femB , play a vital role in the latter stage of the peptidoglycan (PG) biosynthesis process of Staphylococci and can be served as potential targets for developing new antimicrobial therapeutics. , Staphylococcal PG-repeat unit consists of a disaccharide, a pentapeptide stem, and a penta-glycine bridge structure. The PG disaccharide unit (DU) is composed of N -acetyl-glucosamine (NAG) and N -acetyl-muramic acid (NAM) and is conserved among all eubacteria, whereas the pentapeptide stem and bridge structure vary between species .…”
Section: Introductionmentioning
confidence: 99%